Concepción de partida y prácticas profesionales de atención a la discapacidad en Bolivia - Marta García-Domingo; Virginia Fuentes; Maria Carmen Martín-Cano; Yolanda De-la-Fuente (Revista Iberoamericana de Estudios de Desarrollo)
The international advance in the recognition of people with functional diversity’s right is notorious, having been modified its postulates, concepts and models of care being modified. However, progress has been uneven between areas, and the Bolivian context needs a better consolidation of the achievements. In this study, it is intended to know the intervention practices and collective imaginary towards disability in Bolivia, collected through the content analysis of focus group developed with professionals from the context addressed. We find limiting practices towards disability in Bolivia, based on the social imaginary, which result in family overprotection. Prevalence social and institutional isolation towards functional diversity is also identified, based on prejudices, myths and wrong beliefs not yet overcome. Then, medical and social care models coexist, as well as an intervention based on assistance and promotion.